Elucidating the Effect of Antecedents on Consumers’ Green Purchase Intention: An Extension of the Theory of Planned Behavior - Ruangkanjanases, Athapol; You, Jun-Jer; Chien, Shih-Wen; Ma, Yin; Chen, Shih-Chih; Chao, Ling-Chi (Frontiers in Psychology, 2020)
In this study, the extension of theory of planned behavior (TPB) was developed to evaluate the effects of antecedents that influence consumers' intention to buy green food. The effect of nine determinants (i.e. individual benefits, social benefits, willingness-to-pay, environmental responsibility, e-word-of-mouth, values, self-competence, convenience, and environmental literacy) of the green wave on Taiwanese consumers was empirically tested by examining their perception of social responsibility through the TPB. Except for consumer subjective norms, the remaining factors exhibited significant positive correlations with the planned behavior, implying that the voluntary participation aspect of the green wave is considerably more critical than its mandatory social pressure. To diffuse this green wave more effectively, the Taiwanese government should encourage consumers to easily capture the detailed impact of the green wave on the society and allow consumers to use word-of-mouth marketing for the creation of relational value to improve their quality of life.